LOCAL CULTURE BASED POLITICAL COMMUNICATION: CANDIDATE CAMPAIGN STRATEGIES IN MULTICULTURAL COMMUNITIES - Abdul Rahman (Penelitian dan Pengembangan Ilmu, 2025)
Political communication in multicultural societies faces significant challenges due to ethnic, religious, and linguistic diversity, which often leads to ineffective messaging and potential conflict. This research addresses the critical need for a deeper understanding of how political candidates can effectively integrate local cultural values ​​and symbols into their campaign strategies to build stronger relationships with diverse voters. This research aims to investigate how political candidates integrate local cultural values ​​and symbols into their campaign strategies in multicultural communities and to understand the influence of this cultural integration on voter perceptions and engagement. Using a narrative review approach, this research synthesizes extensive literature from Scopus, Web of Science, and Google Scholar, with thematic analysis and narrative synthesis to connect the findings with Cultural Political Communication Theory, Framing Theory, and Symbolic Interactionism. The findings indicate that strategic integration of local cultural values, symbols, and rituals significantly increases voter engagement, trust, and emotional connection. Candidates who authentically incorporate local cultural elements are perceived as more relevant and legitimate, fostering a sense of belonging among voters, and increasing mobilization. Integrating local cultural values ​​and symbols is a fundamental requirement for effective political communication in a multicultural context, strengthening symbolic legitimacy, reducing cultural conflict, and encouraging inclusive political engagement.